'Which of the following is equivalent to the expression (x+3)(x-7)+(x+8)(x+3)?' I use the distributive property and added etc. and my outcome was 2x^2+7x+3. I got the answer as (2x+1)(x+3) but only because it was an answer choice and was equivalent to 2x^2+7x+3. Where did the 1 and 3 come from in (2x+1)(x+3)???
If you use the FOIL (First, Outer, Inner, Last) method on your answer (2x+1)(x+3) you get 2x² + 7x+3. First 2x * x = 2x² Outer 2x *3x = 6x Inner 1 * x= x Last 1 * 3= 3 2x²+6x+x+3 2x² + 7x +3